2018
DOI: 10.5489/cuaj.5377
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance guidelines based on recurrence patterns for upper tract urothelial carcinoma

Abstract: Introduction: Upper tract urothelial carcinoma (UTUC) accounts for 5% of all urothelial tumours. Due to its rarity, evidence regarding postoperative surveillance is lacking. The objective of this study was to develop a post-radical nephroureterectomy (RNU) surveillance protocol based on recurrence patterns in a large multi-institutional cohort of patients. Methods: Retrospective clinical and pathological data were collected from 1029 patients undergoing RNU over a 15-year period (1994-2009) at 10 Canadian acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…72 Postoperative recurrences of UTUCs after RNU also commonly occur at bladder (30%) and locoregional (20%), but only 2-6% at contralateral upper tract. 73 Our subgroup analysis showed that AA exposure was associated with 1.949-fold increased risk of intravesical recurrence of UTUC, and 1.477-fold increased risk in patients diagnosed with AAN. It is worth noting that among the three studies reporting contralateral UTUC recurrence, 49,53,56 the recurrence rates of 0-5% in the control groups were similar to that of 2-6% in the general population.…”
Section: Discussionmentioning
confidence: 62%
“…72 Postoperative recurrences of UTUCs after RNU also commonly occur at bladder (30%) and locoregional (20%), but only 2-6% at contralateral upper tract. 73 Our subgroup analysis showed that AA exposure was associated with 1.949-fold increased risk of intravesical recurrence of UTUC, and 1.477-fold increased risk in patients diagnosed with AAN. It is worth noting that among the three studies reporting contralateral UTUC recurrence, 49,53,56 the recurrence rates of 0-5% in the control groups were similar to that of 2-6% in the general population.…”
Section: Discussionmentioning
confidence: 62%
“…Locoregional or distant recurrence after RNU is not rare and has a high mortality rate once occurred, with limited systemic therapy options available (14). Factors contributing to recurrence are complex and multifocal but include tissue damage, subsequent tumor cell release into the systemic circulation, inflammation, and immune response (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no evidence whether the type of anesthetic technique impacts cancer recurrence or survival in patients with UC of the upper tract (UCUT) undergoing radical nephroureterectomy (RNU). As recurrences after RNU, especially in invasive cases, are not rare, understanding of this association is of clinical importance (14).In this context, we aimed to evaluate cancer recurrence and survival of patients by anesthetic type, utilizing propensity score matching to adjust patient characteristics and minimize preoperative selection bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While little is known about the outcomes of these patients, it may be reasonable to follow existing guidelines for high-risk UTUC. 5 …”
Section: Discussionmentioning
confidence: 99%